THE INFLUENCE OF EYESTALK ABLATION ON THE REGULATION OF HAEMOLYMPH SODIUM CONCENTRATION IN THE PRAWN PENAEUS INDICUS H. MILNE EDWARDS - Kiron, V; Diwan, A D (Indian Journal of Fisheries, 2011)
Removal of the eyestalks of the prawn Penaeiis indiciis resulted in anincrease in the haemolymph-sodium level. This increase was more evident inbilaterally ablated animals. Injection of eyestalk extract into destalked animalshelped them to restore the level almost similar to that of normal animals